Protected Areas and Tourism in Lao PDR : Policy Note - World Bank (World Bank, Vientiane, 2021)
Conservation and tourism contribute to greener economic growth in many countries. Although protected areas have often been viewed as land excluded from economic development for the purposes of environmental conservation, many countries have realized their powerful economic potential through tourism and visitation. In fact, tourism has been an integral part of protected area management since the beginning of their conception. If appropriate policy and technical capacity are established, most protected area professionals argue that both ecosystem protection and tourism development can be implemented concurrently without undermining the objectives of either activity. Lao PDR policy makers have recognized the economic potential of protected areas and seek to develop these sites as a focus of the NSEDP 2015-2019 and the 2030 National Green Growth Strategy, given the globally unique natural heritage of Lao PDR. Not only does tourism in protected areas provide employment opportunities to youth and ethnic peoples, but tourism is also one of the few sectors with high female labor participation above parity (including in Indonesia, Malaysia, Philippines and Thailand).7 Many jobs in protected area management and tourism operations often do not require high levels of education, providing lower barriers to acquire employment for poor communities with properly supported with policy and regulations. Furthermore, these jobs and incomes can often be more sustainable than those in mining or timber activities due to boom and bust cycles from extractive industries. Finally, tourism jobs are often safer than comparable extractive jobs.